Teaching for Engagement: A Phenomenological Inquiry into TVL Pedagogical Practices and Students’ Learning Engagement in a Philippine Public Secondary School - MESSIAN VERDADERO (International Journal of Education, Literacies and Curriculum Studies, 2026)
Student engagement is particularly important in Technology and Livelihood Education (TVL), where meaningful learning requires students to move beyond conceptual understanding toward active participation, practical application, problem-solving, collaboration, and performance-based learning. This qualitative phenomenological study explores the lived experiences of TVL teachers in employing pedagogical practices to foster student engagement in a Philippine public secondary school. Specifically, it investigates how teachers design and facilitate learning experiences, how they perceive and respond to varying levels of behavioral, emotional, cognitive, and agentic engagement, what challenges they encounter in sustaining participation, and how they adapt instruction to learners’ needs and contextual realities. Participants are purposively selected TVL teachers with direct experience teaching practical and competency-based subjects. Data are generated through semi-structured, in-depth interviews and analyzed using Colaizzi’s descriptive phenomenological method. The inquiry is sensitized by constructivist, experiential, and student-engagement perspectives while allowing themes to emerge inductively from participants’ narratives. Particular attention is given to hands-on learning, demonstration and guided practice, collaborative activities, contextualization, differentiated support, learner autonomy, resource constraints, and teacher–student relationships. The study positions engagement not simply as observable participation but as a multidimensional experience shaped by pedagogy, relevance, relationships, competence, and learning conditions. Findings may inform context-responsive TVL instruction, teacher professional development, curriculum implementation, and school-level support for meaningful student participation in practical learning.